PENINGKATAN PARTISIPASI MASYARAKAT MELALUI SOSIALISASI PARTISIPATIF DALAM PENGELOLAAN MANGROVE, AIR, DAN EKOWISATA UNTUK PENGUATAN KETAHANAN PESISIR DI DESA WAWORAHA, KABUPATEN KONAWE - Gandri, La; Indriyani, Lies; Sudia, La Baco; Siwi, La Ode; Manan, Abdul; Teke, Junartin; Muhsimin, Muhsimin; Agusrinal, Agusrinal; Erif, La Ode Muhammad; Hidayat, Herlan; Mandala, Marga; Reichen, Stella (Anoa : Jurnal Pengabdian Masyarakat Sosial, Politik, Budaya, Hukum, Ekonomi, 2025)
The coastal area of Waworaha Village, Konawe Regency, possesses significant potential in mangrove ecosystems, water resources, and coastal landscapes that support the development of community-based ecotourism. However, environmental degradation, low public awareness, and threats from extractive activities and land-use conversion have weakened coastal resilience and community welfare. This community service program aimed to increase community participation in mangrove, water, and ecotourism management as a strategy to strengthen coastal resilience. The method employed participatory socialization through interactive lectures, focus group discussions, and field activities, including mangrove planting and environmental management education. The program involved village officials, youth groups, and coastal communities as the main actors in its implementation. The results indicate an increased community understanding of the ecological functions of mangroves as natural coastal protectors and the importance of water resource conservation for sustainable livelihoods. Community participation in mangrove planting activities and ecotourism planning discussions also increased, as shown by active involvement at every stage of the program. In addition, initial community initiatives emerged to develop mangrove-based ecotourism as an alternative, environmentally friendly, and sustainable source of income. The program also fostered collective awareness of the importance of protecting coastal areas from external environmental pressures. Thus, participatory socialization proved effective in enhancing community engagement in coastal environmental management. Increased participation serves as a crucial foundation for strengthening coastal resilience while opening opportunities to improve community welfare sustainably.